"I Want Them to Feel Safe and to Feel Loved": Collaborating to Teach Social Studies for Middle Level Emergent Bilingual Students - Jaffee, Ashley Taylor (RMLE online : research in middle level education, 2021)
This case study explored how a social studies teacher and a TESOL teacher collaborated to teach an eighth-grade civics and economics course in a diverse classroom with Latinx emergent bilingual students. The researcher employed a theoretical framework of culturally and linguistically relevant citizenship education (CLRCE), which includes five pedagogical principles: pedagogy of community, pedagogy of success, pedagogy of making cross-cultural connections, pedagogy of building a language of social studies, and pedagogy of community-based participatory citizenship. The goals of the study were to identify and understand the perspectives and decision making of the teachers' pedagogy for Latinx youth. Findings revealed the importance of an effective collaborative relationship and using varied pedagogical strategies to support the growth and success of emergent bilingual students in the middle grades. Implications for this study offer middle level social studies and TESOL teachers ideas and strategies for how to support a beneficial collaborative relationship for emergent bilinguals by enacting curricula and pedagogy that are relevant, engaging, equitable, and supportive of the diverse needs of Latinx youth.